2018
DOI: 10.1038/s41467-017-02735-2
|View full text |Cite
|
Sign up to set email alerts
|

Facile storage and release of white phosphorus and yellow arsenic

Abstract: The storage of metastable compounds and modifications of elements are of great interest for synthesis and other, e.g., semiconductor, applications. Whereas white phosphorus is a metastable modification that can be stored under certain conditions, storage of the extremely (light- and air-)sensitive form of arsenic, yellow arsenic, is a challenge rarely tackled so far. Herein, we report on the facile storage and release of these tetrahedral E4 molecules (E = P, As) using activated carbon as a porous storage mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 32 publications
0
38
0
5
Order By: Relevance
“…Luftstabile Polypnictogenkomplexe bieten sehr interessante Alternativen zu herkömmlich verwendetem, hochreaktivem P 4 als Ausgangsmaterialien für die Polypnictogenchemie . Kürzlich haben wir gezeigt, dass der cyclo ‐P 5 ‐Ring von [Cp*Fe(η 5 ‐P 5 )] als Polyphosphorquelle verwendet werden kann.…”
Section: Methodsunclassified
“…Luftstabile Polypnictogenkomplexe bieten sehr interessante Alternativen zu herkömmlich verwendetem, hochreaktivem P 4 als Ausgangsmaterialien für die Polypnictogenchemie . Kürzlich haben wir gezeigt, dass der cyclo ‐P 5 ‐Ring von [Cp*Fe(η 5 ‐P 5 )] als Polyphosphorquelle verwendet werden kann.…”
Section: Methodsunclassified
“…It is interesting to explore the scope of air‐stable starting materials as sources for poly‐pnictogen species as alternatives to the conventionally used and highly reactive P 4 . Recently, we have shown that the cyclo ‐P 5 ring of [Cp*Fe(η 5 ‐P 5 )] could be used as a polyphosphorous source.…”
Section: Figurementioning
confidence: 99%
“…These challenges have recently been addressed by the Scheer group, with a report detailing the preparation of activated carbon-supported As 4 and P 4 (As 4 @C and P 4 @C) which are air-and light-stable and which were employed as synthons in P 4 and As 4 activation chemistry. 18 While the synthesis of As 4 @C still requires the preparation of in situ As 4 solutions, the increased stability of As 4 @C is a marked improvement and has potential for the production of preparative-scale quantities.…”
Section: Pn 4 Activationmentioning
confidence: 99%